Evaluation of the Performance of the General Election Commission Based on the Principles of Clean and Good Governance in the 2024 Election - Mulyadi, Dedi; St May, Nazwa; Hidayat, Shidqi; Egas; Adawiah, Intan (Indonesian Journal of Law and Justice, 2024)
This study evaluates the application of the principles  of clean and good governance by the General Election Commission (KPU) in the implementation of the 2024 Election. Although the KPU is expected to be able to hold transparent, accountable, and participatory elections, the practice still faces a variety of significant challenges. The problem of managing the Permanent Voter List (DPT), uneven distribution of logistics, and the practice of money politics are the main obstacles in achieving this goal. This study uses a normative juridical approach to analyze the extent to which the principles of good governance are applied and their impact on the quality of election implementation. The results of the analysis show that despite progress in voter participation, structural and technical challenges still need to be addressed to improve election integrity. Therefore, reforms are needed in the election process to ensure that the principles of good governance are effectively integrated, in order to achieve better elections with integrity.